The Omani and Bahraini paths to development: Rare and contrasting oil-based economic success stories - Robert Looney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Oman and Bahrain are Middle Eastern success stories. There are some key similarities. Both have followed pragmatic development strategies built on a stable foundation of strengthened governance structures and enhanced economic liberalization. These improvements occurred in somewhat different settings, with Oman developing in a more authoritarian environment, whereas Bahrain enjoyed greater democracy but somewhat less stability. While both countries have relied on oil revenues to support their development efforts, it appears that, in contrast to their less successful oil producing neighbours, each country had just enough oil to do some good, but not enough to do serious damage.
Keywords: O53; 330; Oman; Bahrain; Middle East; GCC; economic development; economic growth; development strategies; Entwicklung; Wirtschaftswachstum; Entwicklungsstrategie; Erdölvorkommen; Oman; Bahrain